Community Based Tourism and Renewable Energy Potential Study of the Sano Nggoang Lake, Flores, Indonesia - Sari, Putu Ayu Amita; Asmoro, Novky; Murtiana, Sri (Research and Social Study Institute, 2025)
Aims: This research employed qualitative methods focused on in-depth research at the Sano Nggoang site. The problem solved by this research is to examine the potential of community-based tourism and renewable energy so that it can bring benefit in economic, social, and environmental benefits for the community.Methods: The methods employed included observation, interviews, and literature review. The goal was to gather information about the potential for community-based tourism, particularly geo-tourism, and renewable energy. This research can then be used to develop the local economy in Sano Nggoang.Result: The results of this study revealed the tourism and renewable energy potential in Sano Nggoang. Attractions include birdwatching, horse riding, village tours, and forest tours. Available amenities include hot springs and homestays. Renewable energy potential includes geothermal energy and renewable energy. All of this potential can be developed through community-based tourism, thereby providing economic benefits to the residents of Sano Nggoang.Conclusion: The conclusion is that there is considerable potential in renewable energy and geotourism. However, it must be developed collaboratively with the community using a community-based tourism concept. This can then be further developed and implemented within the community to provide sustainable benefits.